Efektivitas Media Pembelajaran Berbasis Tiktok Pada Mata Pelajaran Informatika Kelas X TKJ - Wahyuni, Rahmi; Irsyadunas, Irsyadunas; Alfiriani, Adlia (Jurnal Informatika, 2023)
The rapid development of technology at this time, educators are expected to be able to create interesting and innovative learning media for students. So that it has an impact on student learning outcomes later. One of the learning media that can be utilized is the TikTok application. The TikTok application is an application in the form of short videos that are packaged properly. And the majority of users are millennials and school children. The purpose of this study was to determine the effectiveness of TikTok-based learning media used in informatics class X TKJ at SMK Negeri 2 Padang. The method used is an experiment. By using One Group Pretest-Posttest Design. The sample is determined by simple random sampling technique. For data analysis techniques using the analysis prerequisite test, namely the normality test, hypothesis testing using the paired sample test with a result of 0.000, and the N-Gain test. Based on the results of the N-Gain test in the experimental class, it was obtained at 63,765 or 63.7%. In the interpretation of the N-Gain percentage category if 56-75% is said to be quite effective. So the N-Gain score of 63.7% is said to be quite effective. So that the effectiveness of TikTok-based learning media in class X TKJ informatics subjects at SMK Negeri 2 Padang is quite effective.